Prospecção de cylindrospermopsis raciborskii em reservatórios no Ceará e efeitos da depleção de nutrientes na sua concentração celular - Barros, Mário Ubirajara Gonçalves (2013)
The water quality of Brazilian reservoirs has been harmful due to the intense process of eutrophication. Wastewater, agriculture and intensive farming favor this phenomenon by introducing into the aquatic environment high concentrations of nutrients, particularly nitrogen and phosphorus. Eutrophication of water affect the public water supply because induces proliferation of cyanobacteria potentially toxins producer. This study aimed to perform a mapping of cyanobacteria potentially toxins producer, specifically Cylindrospermopsis raciborskii, in reservoirs used for public supply in the state of Ceará. Data were collected in the central laboratory of Water and Wastewater Company of Ceará (CAGECE). We also evaluated the effect of depletion of limiting nutrients in the growth of C. raciborskii T3. The experiments were performed using as the culture medium ASM-1 and variations of it with the removal of 75% and 50% of phosphorus and nitrogen from its initial composition. Cultures were grown in axenic conditions and maintained under constant light intensity of 6.75μ.mol.m-2.s-1, subjected to photoperiod of 12h: 12h and 24 ± 2 º C. The mapping of phytoplankton in reservoirs studied showed dominance of cyanobacteria, often greater than 90% of the total cell concentration. Regarding the cyanobacterium C.raciborskii, its presence was evident in all reservoirs studied, with less representation in Cedro (30%) and higher in Carmina (98%). In all reservoirs except Cedro, the presence of the genus C. raciborskii was on average greater than 70% throughout the study period. The dominance of this species was found in three reservoirs: Acarape do Meio (92%), Serafin Dias (89%) and Coronel (73%) and two reservoirs, Sitios Novos and Cedro, this species did not dominated in any campaign. The results also showed that the nitrogen-depleted cultures showed significantly lower growth relative to other experiments, reaching the stationary phase sooner and at lower cell concentrations. Cultures with depletion of phosphorous (75%P and 50%P) showed more pronounced growth curves, showing that the element nitrogen was limiting the growth of C. raciborskii in this experiment.